New National Drug Policy in Iran leading to Expanded Pharma¬ceutical Market and Extended Access of Public to Medicines - R Dinarvand (Tehran University of Medical Sciences, 2009)
Pharmaceutical market in Iran has been expanding since 2001 when the new development act was approved in the parliament of the Islamic republic of Iran. The pharma market size has annually increased 6.8% in terms of volume and 18.5% in terms of value.  However, the growth rate of imported items has been greater than locally produced items both in terms of value and volume. This may be mainly due to the introduction of free market regulations at macroeconomic point of view that has influenced the pharmaceutical market as well. The expansion of pharmaceutical market is welcomed by the industry which is investing heavily in the manufacturing and research and development capacity of pharma sector in Iran. However it does also mean greater access of the public to essential and vital medicines. In the same situation the presence of extra choices in the market may be a challenge for the local industry as the demand for higher quality medicines grows. Market forces are always a challenge for the advocacy of rational prescription and use of medicines.